2009
DOI: 10.1021/ar800250h
|View full text |Cite
|
Sign up to set email alerts
|

Gd−Hydroxypyridinone (HOPO)-Based High-Relaxivity Magnetic Resonance Imaging (MRI) Contrast Agents

Abstract: ConspectusMagnetic resonance imaging (MRI) is a particularly effective tool in medicine because of its high depth penetration (1 mm to 1 m) and ability to resolve different soft tissues. The MRI signal is generated by the relaxation of in vivo water molecule protons. MRI images can be improved by administering paramagnetic agents, which increase the relaxation rates of nearby water protons, thereby enhancing the MRI signal. The lanthanide cation Gd 3+ is generally used because of its favorable electronic prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
166
1
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(170 citation statements)
references
References 48 publications
2
166
1
1
Order By: Relevance
“…The two vinylic protons on the pyridinone ring appear as doublets with J HH = 7.2 Hz at δ 7.41 and 6.04 ppm. All solution spectroscopic data are consistent with previously prepared hydroxypyridinone derivatives that have a localized alkene within the ring and elemental analysis confirms the majority of the product is the neutral species [1][2][3]. However, we were able to obtain one single crystal of the hydrochloride salt for an X-ray diffraction study, the molecular structure of which is shown in Figure 2.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The two vinylic protons on the pyridinone ring appear as doublets with J HH = 7.2 Hz at δ 7.41 and 6.04 ppm. All solution spectroscopic data are consistent with previously prepared hydroxypyridinone derivatives that have a localized alkene within the ring and elemental analysis confirms the majority of the product is the neutral species [1][2][3]. However, we were able to obtain one single crystal of the hydrochloride salt for an X-ray diffraction study, the molecular structure of which is shown in Figure 2.…”
Section: Resultssupporting
confidence: 86%
“…Hydroxypyridinones are an important class of heterocyclic compounds that are being examined as possible agents for sequestering and removing toxic metal ions [1][2][3]. For instance, Deferiprone (Figure 1b) belongs to a class of 3-hydroxy-4-pyridinone compounds derived from maltol ( Figure 1a), a natural flavor enhancer, which is being investigated for its use as a chelating agent for the treatment…”
Section: Introductionmentioning
confidence: 99%
“…B. Relaxivity, nuclear magnetic dispersion profiles NMRD measurements provide valuable insights and information about the dynamic, and structural parameters of MRI CAs that influence relaxivity. [3][4][5]8 The r 1 NMRD profile (proton Larmor frequency ¼ 1.15 to 61.73 MHz) for proton relaxivity at 25 C for individually dispersed Gd-SWCNTs in 1% Pluronic F127 is presented in Figure 3(a). Gd-SWCNTs have distinctly different r 1 NMRD profiles than Gd 2 O 3 nanoparticles dispersed in 1% Pluronic F127 solution (Figure 3(b)), and Gd 3þ -based small molecular and macromolecular complexes.…”
Section: Resultsmentioning
confidence: 99%
“…7 Theoretical studies predict the possible development of novel MRI CAs with 50-100 times greater relaxivity than current clinical gadolinium-chelate complexes. 4,8 Thus, a major focus of MRI CA research has been to utilize relaxometry and other characterization tools to further understand the molecular, structural, dynamic, and magnetic properties of MRI CAs that affect water proton relaxation times. 8 This improved understanding facilitates the development of rational synthetic design strategies to improve the relaxivity of next-generation MRI CAs.…”
mentioning
confidence: 99%
“…To address a critical, unmet medical need, we developed a strategy in our creation of an MRI contrast agent using protein design and modification to increase relaxivity without compromising metal binding affinity/stability, selectivity, and pharmacokinetic properties that are dramatically different from previously reported approaches (25)(26)(27)(28)(29)(30)(31)(32). Building on our previous success in improving relaxivity by designing a Gd 3+ -binding site into a scaffold protein CD2 and with a goal of improving metal binding affinity, we report a method to develop the protein contrast agent ProCA32 by converting the natural Ca 2+ -binding protein, parvalbumin, into a Gd 3+ -binding protein that is also PEGylated.…”
Section: Discussionmentioning
confidence: 99%